Optimal calculation of the pair correlation function for an orthorhombic system - Roehrig, Kai A. F.; Kuehne, Thomas D. (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2013)
We present a computational method to calculate arbitrary pair correlation functions of an orthorhombic system in the most efficient way. The algorithm is demonstrated by the calculation of the radial distribution function of shock compressed liquid hydrogen. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20